Urban environment and unequal urban environmental policies: a case study in Argentina (Sustainability in Debate, 2024)
This study analyses different and unequal urban environmental problems in the city of Posadas (Argentina), where there are different social practices of environmental care and management according to neighbourhoods. The aim was to understand and describe the action or lack of action of environmental legislation or policy concerning different urban areas. Based on a quantitative survey, the spatial context of the neighbourhoods was linked to environmental problems and policies, environmental care practices, opinions, attitudes, and social self-management processes in each neighbourhood. It describes how people living in the poorest neighbourhoods are disproportionately exposed to adverse environmental conditions and risks. Neighbourhoods in urban spaces with high environmental quality have more services, resources and government attention, while the most disadvantaged neighbourhoods in the city are also the least favoured by policies and deficient urban structures.